Livestock Development Based on Local Resources to Decreasing of Dependency Level and Improve of Community Economics - Hartoko Hartoko (Animal Production: Indonesian Journal of Animal Production, 2001)
To decrease the level of dependency on import goods, it is necessary to develop local based animal husbandry. This action has an important meaning in order to improve community economics in Indonesia.  Some ideas to motivate the development of the local based animal husbandry, are: first, mapping of the local resources, including specific superior local animals. Second, to support the continuity of feedstuffs production. Third, germ plasm / genuine animal conservation. Fourth, publication  of popular scientific magazine and , Fifth, development of integrated farming system, horizontally as well as vertically, and market strategi.  Finally, the key factor is human resources, so the empowerment of farmers is necessary to grow- up the local based animal husbandry. (Animal Production 3(2): 74-82 (2001)